Crystal structure and morphology of band-gap engineered titania and titanates via hydrothermal synthesis - Lim, Linda Ying Wen. (2010)
Titania (TiO2) and sodium titanate nanostructures were synthesized by hydrothermal method with titanium disulfide (TiS2) as the starting material. The experimental results revealed that TiS2-derived sodium titanate compounds could be synthesized under a relatively low alkaline concentration (1 M NaOH) and short duration (6 hours). At highly acidic condition, rutile TiO2 nanorods were obtained. Anatase TiO2 nanoparticles were obtained under pH values ranging from 2 to 13. Sodium titanate nanobelts were synthesized under highly alkaline conditions. FTIR analysis confirmed the phase change as the pH of the reacting medium increased from highly acidic to highly alkaline condition. In addition, phase changes from sodium titanate to anatase were observed as the synthesis temperature was increased from 120°C to 220°C. The optical properties of the as-synthesized sodium titanate were also enhanced in the visible light region by decreasing the synthesis temperature. The adsorption of methylene blue (MB) on the as-synthesized sodium titanate nanobelts fitted well with the Langmuir model, with a maximum adsorption capacity of 312.5 mg g-1. The kinetics of MB adsorption was found to follow the pseudo-second-order kinetic model. Sodium titanate nanostructures synthesized in 1 M NaOH at 120°C was also found to be visible-light active in the photodegradation of MB solution. This study demonstrates a simple method to control the types, morphologies and optical properties of titanium-based oxides with excellent adsorption of MB and visible-light activity exhibited by the sodium titanate nanostructures.